Law and Development in East and South-East Asia - Antons, Christoph (Taylor & Francis, 2003)
During the 1980s and 1990s Asian 'developmental states' attracted much attention in political science and economics literature, but the role of law in the economic development was neglected. It was only after the Asian crisis of 1997 that many analysts began to focus on a lack of regulation and transparency as a major factor triggering the crisis. The crucial questions now are how successful the current reforms will be, and which features of the Asian approach to commercial law will be resistant to reform pressures. This book examines the prospects for commercial law reform in Asia, giving particular attention to Japan and Singapore, as frequently cited role models for Asian developmentalism, and also examining development related business laws in countries such as China, Korea, Indonesia, Malaysia, Vietnam and the Philippines.